Globalization and financial development of the state (Journal of Economic Research & Business Administration, 2016)
In modern science, the term «globalization» has become a stable and a key concept, which does not manage the study of many problematic issues and not just in the economy. Active research the nature and role of globalization is not only the scale but also the breadth of areas: it is seen as an economic and a social, political, interpersonal, demographic, and many other aspects. The study of scientific publications, materials and presentations on these issues has enabled us to conduct the following classification of the main economic approaches to the interpretation of the essence of globalization and its role in the global community and the development of national economies. Globalization – this is a special process of development of the society, which is characterized by activation of movement and the flow of capital, goods, services, technology, labor, and with them the traditions and cultures as a result of the search of more favorable conditions for their development. In numerous writings globalization process can be divided into several stages: the stage of colonialism, the stage of industrialization and the rise of capitalism at the beginning of the XIX century, as well as the current stage of globalization.
Keywords: globalization; economics; finance; financial development of the state.